Active-site plasticity revealed in the asymmetric dimer of AnPrx6 the 1-Cys peroxiredoxin and molecular chaperone from Anabaena sp. PCC 7120. Issue 1 (December 2017) - Mishra, Yogesh; Hall, Michael; Locmelis, Roland; Nam, Kwangho; Söderberg, Christopher; Storm, Patrik; Chaurasia, Neha; Rai, Lal; Jansson, Stefan; Schröder, Wolfgang; Sauer, Uwe
Abstract Peroxiredoxins (Prxs) are vital regulators of intracellular reactive oxygen species levels in all living organisms. Their activity depends on one or two catalytically active cysteine residues, the peroxidatic Cys (CP ) and, if present, the resolving Cys (CR ). A detailed catalytic cycle has been derived for typical 2-Cys Prxs, however, little is known about the catalytic cycle of 1-Cys Prxs. We have characterized Prx6 from the cyanobacteriumAnabaena sp. strain PCC7120 (AnPrx6) and found that in addition to the expected peroxidase activity, AnPrx6 can act as a molecular chaperone in its dimeric state, contrary to other Prxs. The AnPrx6 crystal structure at 2.3 Å resolution reveals different active site conformations in each monomer of the asymmetric obligate homo-dimer. Molecular dynamic simulations support the observed structural plasticity. A FSH motif, conserved in 1-Cys Prxs, precedes the active site PxxxTxxCp signature and might contribute to the 1-Cys Prx reaction cycle.